Kinetic Spectrophotometric Determination of Trace Sodium Lauryl Sulfate Based on Catalytic Oxidation of Butyl Rhodamine B - Ma, Yu-Qin; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
In 1.0 M of sulfuric acid medium, sodium lauryl sulfate has a catalytic effect on the oxidation reaction of butyl rhodamine B (BRhB) by potassium periodate at 80 ºC. Based on this principle, a novel catalytic kinetic method for the determination of sodium lauryl sulfate is developed. A linear range was presented over the range of 0.10-1.10 μg/mL for sodium lauryl sulfate at 552 nm. The detection limit of the method was 0.035 μg/mL for sodium lauryl sulfate. The method has been satisfactorily applied to the determination of sodium lauryl sulfate in water sample and detergent with satisfactory results.